A Novel Approach in the WIMP Quest: Cross-Correlation of Gamma-Ray Anisotropies and Cosmic Shear - Marco Regis (Acta Polytechnica CTU Proceedings)
We present the cross-correlation angular power spectrum of cosmic shear and gamma-rays produced by the annihilation/decay of Weakly Interacting Massive Particle (WIMP) dark matter (DM), and by astrophysical sources. We show that this observable can provide novel information on the composition of the Extra-galactic Gamma-ray Background (EGB), since the amplitude and shape of the cross-correlation signal depend on which class of sources is responsible for the gamma-ray emission. If the DM contribution to the EGB is significant (at least in a definite energy range), although compatible with current observational bounds, its strong correlation with the cosmic shear (since both signals peak at large halo masses) makes such signature potentially detectable by combining Fermi-LAT data with forthcoming galaxy surveys, like Dark Energy Survey and Euclid.